Additional considerations and recommendations for the quantification of hand-grip strength in the measurement of leg power during high-intensity cycle ergometry - Baker, J. S.; Davies, B. (Research in Sports Medicine, 2009)
The purpose of this study was to further examine the influence of hand-grip strength on power profiles and blood lactate values during high-intensity cycle ergometry. Fifteen male subjects each completed a 20-second cycle ergometer test twice, in a random manner, using two protocols, with a hand grip (WG), and without hand grip (WOHG). Hand-grip strength was quantified prior to exercise using a hand-grip dynamometer. Capillary (earlobe) blood was collected at rest, immediately following exercise, and 5 minutes postexercise. In the WG protocol, mean (±SD) blood lactate concentrations were 1.11 ± 0.7 mmol.l -1, 3.68 ± 1.2 mmol.l -1, and 8.14 ± 1.3 mmol.l -1, respectively. During the WOHG protocol, blood lactate values recorded were 0.99 ± 0.9 mmol.l -1, 3.68 ± 1.1 mmol.l -1, and 6.62 ± 0.9 mmol.l -1, respectively. Differences in lactate concentrations were found (P < 0.05) from rest to 5 minutes postexercise for both groups. Differences in concentrations also were observed between groups at the 5-minutes postexercise stage. Peak power output and fatigue index values also were greater using the WG protocol (792 ± 73 W vs. 624 ± 66 W; 38 ± 6 vs. 24 ± 8 W respectively; P< 0.05). No differences were recorded for mean power output (MPO) or work done (WD) between experimental conditions. These findings suggest that the performance of traditional style leg cycle ergometry is influenced by a muscular contribution from the upper body and by upper body strength.